“United States shall so legislate and act as to secure the permanent prosperity and happiness of said Indians”: Policy Implications of the Apache Nation’s 1852 Treaty - Welch, John (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
As binding contracts among sovereigns, treaties between Indigenous and Western Nations set parameters for and guide policies that recognize Indigenous Peoples’ rights and that harmonize those rights with non-Indigenous interests. Because treaties engage specific terms, parties, and geographies, detailed analyses of treaty texts and historical contexts are required foundations for understanding Treaty Rights and for proposing policy reforms. The litigious “Save Oak Flat” battle over the Resolution Copper mine proposed for Apache Nation Treaty Territory in present day Arizona prompts close scrutiny of the 1852 Treaty between the United States and the Apache Nation. Because the 1852 Treaty guarantees rights to both parties, it provides mandates and suggests co-management mechanisms to safeguard Apache Nation Treaty Territory and Apache rights to religious practice free from threats of sacred site destruction.